The Impact of Oil on the Emergence of Regional Conflict in the Gulf Region: "The Buraimi Oasis as a model" During the Period 1946-1974 - Alketbi, Subaiha; Al Bedwawi, Saif (Al-Adab Journal, 2025)
This study examined the impact of oil on the emergence of regional conflict in the Arabian Gulf, using the Buraimi Crisis (1946-1974) as a case study. The study sought to highlight oil's pivotal role in fueling the conflict between regional and international powers over the strategically and economically important Buraimi Oasis.The study adopted a historical approach, examining sources and historical documents related to the crisis. The study concluded that the discovery of oil in Buraimi transformed it into a focal point of conflict, as Saudi Arabia, Oman, and Abu Dhabi sought to assert control over it, with the support of international powers such as Great Britain.The study also highlighted the role played by Sheikh Zayed bin Sultan Al Nahyan in peacefully resolving the crisis through his intensive diplomatic efforts. The study concluded that oil was a critical factor in the emergence of regional conflict in the Gulf region and emphasized the importance of diplomacy and dialogue in resolving disputes.